Roles of zinc-fingers and homeoboxes 1 during the proliferation, migration, and invasion of glioblastoma cells - Ryuk-Jun Kwon; Myoung-Eun Han; Youn-Jae Kim; Yun Hak Kim; Ji-young Kim; Liangwen Liu; Woong Heo; Sae-Ock Oh (Tumor Biology)
Zinc-fingers and homeoboxes 1 (ZHX1) is a nuclear transcription repressor and known to be involved in cell differentiation and tumorigenesis. However, the pathophysiological roles of ZHX1 have not been characterized in glioblastoma. We examined ZHX1 expression in glioblastoma patients’ tissues and analyzed overall survival of the patients based on expression level of ZHX1. We also examined the effects of ZHX1 on proliferation and motility of glioblastoma cells. In silico analysis and immunohistochemical studies showed that the messenger RNA and protein expressions of ZHX1 were higher in the tissues of glioblastoma patients than in normal brain tissues, and that its overexpression was associated with reduced survival. In vitro, the downregulation of ZHX1 decreased the proliferation, migration, and invasion of glioblastoma cells, whereas its upregulation had the opposite effects. In addition, we showed ZHX1 could contribute to glioblastoma progression via the regulations of TWIST1 and SNAI2. Taken together, this study demonstrates that ZHX1 plays crucial roles in the progression of glioblastoma, and its findings suggest that ZHX1 be viewed as a potential prognostic maker and therapeutic target of glioblastoma.